A new organosilylated hydrogel as loss control materials: Synthesis, characterization, and evaluation - Tasque, Joana Elisa (2023)
A crosslinked polymer from acrylamide (AM) and 1,3-divinyltetramethyldisiloxane was synthesized. The resulted polymer was characterized by NMR and FTIR-ATR. Their swelling and sealing capacity were assayed, and it was observed a percentage hydration of 1700% after 4 h of hydration and then, its hydration rate decreased, acquiring a maximum hydration of 2300% at 168 h. Also, the synthesized hydrogel was studied to evaluate his performance as loss control material (LCM) for petroleum industry. The performance in sand bed tester and High Pressure and high temperature (HPHT) cell essays, obtained at different pressures, demonstrated that the hydrogel is a good candidate for application as LCM. Additionally, it is combinable with additional particulate materials, showing synergy in their properties.